PB5. Perspective taking during laughter perception. Issue 8 (August 2018) - Wildgruber, D.; Ritter, J.; Jacob, H.; Kreifelts, B.
Abstract : Laughter is a powerful signal to express social acceptance or rejection. Recordings of distinct laughter types (taunting, tickling, joyful) can be identified well above chance level even without any contextual information (Szameitat et al., 2009a; Ritter et al., 2015 ) and specific patterns of brain activation were identified during processing of distinct laughter types (Szameitat et al., 2010; Wildgruber et al., 2013 ). Here, we evaluated the effect of perspective taking on laughter processing. Stimuli comprised 60 videos of laughing faces including three different laughter types (joyful, tickling, taunting). After stimulus presentation participants judged the intention of the laugher on a four-point scale ranging from strongly socially inclusive to strongly socially exclusive. In one session, the participants were asked to imagine they were directly addressed by the laughter (SELF), during the other session they imagined a different person was addressed (OTHER). Sixty participants (30 women) took part in a behavioral study and 26 individuals (13 women) participated in an fMRI-study (3 T, Siemens Prisma). Joyful laughter was rated as the most inclusive and taunting as the most exclusive type. Under the SELF-condition the difference between both decreased as compared to the OTHER-condition. At the neurobiological level the main effect of task (SELF > OTHER) was linked to stronger activation within the bilateral fronto-temporal social perception network ( p < 0.05, uncorrected) presumably reflecting increased attention towards social cues. Moreover, an interaction effect (task × laughter type) with stronger responses during SELF-directed taunting laughter (vs. friendly) as compared to OTHER-directed laughter emerged within the bilateral amygdalae ( p < 0.01, uncorrected), whereas stronger responses during OTHER-directed taunting laughter (vs. friendly) as compared to SELF-directed laughter were observed within the left dorsolateral prefrontal cortex ( p < 0.05, corrected). The observed effects highlight the usefulness of laughter as a highly prevalent social signal for research on the interrelations of social cue perception and perspective taking.